2023
DOI: 10.1039/d2gc02783f
|View full text |Cite
|
Sign up to set email alerts
|

Improving methanol assimilation in Yarrowia lipolytica via systematic metabolic engineering combined with compartmentalization

Abstract: Renewable methanol is an attractive non-food feedstock that can replace sugar-based raw materials for biochemicals production. However, the metabolic construction of synthetic methylotrophy to utilize methanol for cell growth and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…As shown in Fig. 2, the ratios of the peaks at around m/z 103 and m/z 104 are almost the same with the unlabeled standard sample and the 13 C-HCHO samples. This finding indicated that formaldehyde is an essential precursor in the synthesis of 2,4-DHB, and the coupling of formaldehyde with endogenous pyruvate derived from glycolysis provides an excellent opportunity for the synthesis of the valuable chemical 2,4-DHB.…”
Section: Validation and Optimization Of The Formaldehyde-based 24-dhb...mentioning
confidence: 52%
See 4 more Smart Citations
“…As shown in Fig. 2, the ratios of the peaks at around m/z 103 and m/z 104 are almost the same with the unlabeled standard sample and the 13 C-HCHO samples. This finding indicated that formaldehyde is an essential precursor in the synthesis of 2,4-DHB, and the coupling of formaldehyde with endogenous pyruvate derived from glycolysis provides an excellent opportunity for the synthesis of the valuable chemical 2,4-DHB.…”
Section: Validation and Optimization Of The Formaldehyde-based 24-dhb...mentioning
confidence: 52%
“…Then, the fermentation broth was transferred (1% inoculum) into a 250 mL flask containing 50 mL of M9 medium supplemented with 100 μg mL −1 ampicillin and incubated at 37 °C. When the OD 600 reached about 0.8, 0.5 mM IPTG and 5 mM formaldehyde or 13 C-HCHO were added to induce gene expression. After induction at 30 °C for 12 h, 50 mM formaldehyde, 13 C-HCHO was added as a substrate.…”
Section: Determination Of 13 C-labeled Intracellular Metabolitesmentioning
confidence: 99%
See 3 more Smart Citations